PENGARUH PENDIDIKAN THAHÃRAH TERHADAP SIKAP HIDUP SEHAT SANTRI PONDOK PESANTREN DI PEKALONGAN - Abdul Khobir (Jurnal Penelitian, 2010)
Many institutions or individuals use religious symbol or attributes, but the attitudes that they perform or express are contra-productive with what they wear, including cleanliness. This research tries to investigate the correlation between education on cleanliness (thaharah) with health behavior of student in two Islamic boarding schools (pesantren), urban and sub-urban. Based on data analysis using anava two ways, this research reveals that there is different influence of education on cleanliness between two Islamic boarding schools, between two different genders, and there is a relation between education on cleanliness and health attitude of students in two Islamic boarding schools if it is viewed based on students’ gender.